The laboratory as a tool for innovation in social science teaching - Corchado Castillo, Ana I.; Blanco Carrasco, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article analyzes the results of a teaching innovation project developed during the academic year 2021-2022, whose main objective was to assess the need to in- clude a compulsory subject of mediation and collaborative conflict resolution in the degree in Social Work at UCM. To this end, an international working group has been formed in the form of an Ideas Lab that has developed a research combining quan- titative (questionnaire) and qualitative (Design Thinking) tools, whose results have allowed to develop a proposal that has been submitted to the dean's office for consideration in the future modification of the degree. But undoubtedly, the most remarkable thing is that through the laboratory it has been possible to guaran- tee essential elements for the quality of the training of our university community: transversality, transdisciplinarity, internationalization and transfer of knowledge.